(untitled) (Ozone Therapy Global Journal, 2014)
The inflammatory diseases of female genital organs are numbered among the most frequent pathologies of fertile women. In order to increase the efficiency of treatment and to avoid possible side effects we have used intrauterine irrigations with ozonized dist i l led water in case of acut e endomet ritis. This method of t reat me nt has b een provided to 60 patients wi th postnata l and postabortive endometritis. Based on the received results, we have dr aw n a c onc lusion that in t he course of treatment all patients showed an impr ovement in general s tate, bod y tempe rature re turn ed to nor ma l, sympto ms o f in toxication decreased, slee p and appetite got better, pain syndrom disappeared faster, pathological discharges were eliminated. The results of laboratory investigations have demonstrated a credible decrease in ESR, normalization of leukoc yte number, a de crease in circulating immune complexes . Thus, for treatment of endometritis we may recommend the given method o f ozone ther apy to be used in combination with a basi c a nti-inflammatory therapy.